2021
DOI: 10.1063/5.0043903
|View full text |Cite
|
Sign up to set email alerts
|

Wide range temperature-dependent (80–630 K) study of Hall effect and the Seebeck coefficient of β -Ga2O3 single crystals

Abstract: Investigation of Seebeck coefficient in ultra-wide bandgap materials presents a challenge in measurement, nevertheless, it is essential for understanding fundamental transport mechanisms involved in electrical and thermal conduction. β-Ga2O3 is a strategic material for high power optoelectronic applications. Present work reports Seebeck coefficient measurement for single crystal Sn doped β-Ga2O3 in a wide temperature range (80-630 K). The non-monotonic trend with large magnitude and negative sign in the entire… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
3
9
0
Order By: Relevance
“…It is worthy to note that the increasing rate of ZT also and mobility of 90 cm 2 V À1 s À1 . 45 By using this carrier mobility and carrier concentration, our calculation gives a ZT value of 0.007 at 300 K, which is in good agreement with the results of Kumar et al This further confirms the reliability of our calculations, and a high carrier mobility and optimal carrier concentration are both necessary to achieve good thermoelectric performance. Based on the above results and discussion, it can be concluded that an elaborate tailoring of the electrical transport properties of b-Ga 2 O 3 to attain the optimal carrier concentration is the first and the most important step for high thermoelectric performance.…”
Section: Phonon Transport Propertiessupporting
confidence: 90%
See 4 more Smart Citations
“…It is worthy to note that the increasing rate of ZT also and mobility of 90 cm 2 V À1 s À1 . 45 By using this carrier mobility and carrier concentration, our calculation gives a ZT value of 0.007 at 300 K, which is in good agreement with the results of Kumar et al This further confirms the reliability of our calculations, and a high carrier mobility and optimal carrier concentration are both necessary to achieve good thermoelectric performance. Based on the above results and discussion, it can be concluded that an elaborate tailoring of the electrical transport properties of b-Ga 2 O 3 to attain the optimal carrier concentration is the first and the most important step for high thermoelectric performance.…”
Section: Phonon Transport Propertiessupporting
confidence: 90%
“…The room temperature mobility is 101 cm 2 V À1 s À1 . According to the study of the b-Ga 2 O 3 single crystal by Kumar et al, 45 the relationship between mobility and temperature is m e p T À0.70 when the temperature is higher than 220 K. 45 By fitting the calculated results, we get the relationship of electron mobility with temperature as m e p T À0. 67 , which shows an excellent agreement with the experimental results.…”
Section: Electrical Transport Propertiesmentioning
confidence: 99%
See 3 more Smart Citations